Energy saving schemes in the technologies of manufacturing products granulated by crystallization of melts drops - Y. A. Taran; M. K. Zakharov (Тонкие химические технологии, 2011)
Schemes of energy saving by utilization of phase transformation heat in processes of granulation and capsulation by crystallization of melts drops were suggested and analyzed. The positive effects of energy saving due to introduction of heat pumps into the technological scheme were estimated. The calculations were made for granulation and capsulation of ammonium nitrate, carbamide, KNO3, NaOH, KOH, sulfur, and slag of phosphorus furnaces and blast-furnaces.